Pertumbuhan Tunas Sansevieria trifaciata Prain ‘Laurentii’ pada Beberapa Komposisi Media Tanam dan Konsentrasi GA3 - Tatiek Kartika Suharsi; Namira Andiani (Departemen Agronomi dan Hortikultura, 2013)
The objectives of this research was to know the effect of growing media composition and concentration level of GA3, on growth of Sansevieria trifaciata Prain ‘Laurentii’ shoots. The research was conducted at Leuwikopo Experiment Field, IPB, Darmaga from March until July 2011. The research used Randomized Complete Block Design (RCBD) with two factors and three replications, Sansevieria trifaciata Prain ‘Laurentii’ variegata leafs used in this research. The first factor was growing medium composition, they were charcoal husk:soil:compos (1:2:1); pasir malang:soil:compos (2:2:1); cocopeat:soil:compos (3:2:1). The second factor was concentration of GA3 treatment consist of three level, 0 ppm; 100 ppm; 500 ppm. Charcoal husk and pasir malang gave good effect for growth of young shoots. Concentration of GA3 until 500 ppm had no significant effect on young shoot growth but it had significant effect on roots growth. The best interaction treatment effect on young shoots growth was charcoal husk medium and 500 ppm concentration of GA3.Keywords: charcoal husk, cocopeat, leaf cutting, pasir malang